Doppler velocimetry on microparticles trapped and propelled by laser light in liquid-filled photonic crystal fiber - Garbos, M. K.; Euser, T. G.; Schmidt, O. A.; Unterkofler, S.; Russell, Philip St. John (Optics Letters, 2011)
Laser Doppler velocimetry is used to measure very accurately the velocity and position of a microparticle propelled and guided by laser light in liquid-filled photonic crystal fiber. Periodic variations in particle velocity are observed that correlate closely with modal beating between the two lowest order guided fiber modes.
EAM Import::2019-03-13